1997
DOI: 10.1152/jappl.1997.83.5.1482
|View full text |Cite
|
Sign up to set email alerts
|

Impaired muscle glycogen resynthesis after a marathon is not caused by decreased muscle GLUT-4 content

Abstract: Our purpose was to investigate whether the slow rate of muscle glycogen resynthesis after a competitive marathon is associated with a decrease in the total muscle content of the muscle glucose transporter (GLUT-4). Seven well-trained marathon runners participated in the study, and muscle biopsies were obtained from the lateral head of the gastrocnemius muscle before, immediately after, and 1, 2, and 7 days after the marathon, as were venous blood samples. Muscle GLUT-4 content was unaltered over the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…However, a subsequent study by Asp et al (1997) [3] which investigated muscular injury in trained runners following participation in a standard marathon failed to show a decrease in GLUT4 content.…”
Section: Glucose Uptake and Insulin Sensitivitymentioning
confidence: 96%
See 4 more Smart Citations
“…However, a subsequent study by Asp et al (1997) [3] which investigated muscular injury in trained runners following participation in a standard marathon failed to show a decrease in GLUT4 content.…”
Section: Glucose Uptake and Insulin Sensitivitymentioning
confidence: 96%
“…However, a number of studies have shown muscle glycogen synthesis to be impaired following eccentric exercise resulting in EIMD [2][3][4]6,14,17,18,20] . Some studies have even shown muscle glycogen concentrations to be lower 24-48 hours later compared to immediately after the completion of the exercise bout [48] , suggesting the complete inhibition of glycogen synthesis.…”
Section: Glycogen Metabolismmentioning
confidence: 99%
See 3 more Smart Citations